Veteran athlete - Reaburn, P. (Modern Athlete & Coach, 2014)
Abstract: The article offers the author's view on enhancement recovery of veteran athletes in training sessions and races. He examines the application of recovery strategies in veteran athletes. A table is also presented that lists the high and medium-high commonly used recovery strategies by veteran athletes, including contrast water treatment, stretching, and sleep.